Role of the renin-angiotensin system in the development of COVID-19-associated neurological manifestations - Méndez-García, Lucía A.; Escobedo, Galileo; Minguer-Uribe, Alan Gerardo; Viurcos-Sanabria, Rebeca; Aguayo-Guerrero, José A.; Carrillo-Ruiz, José Damián; Solleiro-Villavicencio, Helena (Frontiers in Cellular Neuroscience, 2022)
SARS-CoV-2 causes COVID-19, which has claimed millions of lives. This virus can infect various cells and tissues, including the brain, for which numerous neurological symptoms have been reported, ranging from mild and non-life-threatening (e.g., headaches, anosmia, dysgeusia, and disorientation) to severe and life-threatening symptoms (e.g., meningitis, ischemic stroke, and cerebral thrombosis). The cellular receptor for SARS-CoV-2 is angiotensin-converting enzyme 2 (ACE2), an enzyme that belongs to the renin-angiotensin system (RAS). RAS is an endocrine system that has been classically associated with regulating blood pressure and fluid and electrolyte balance; however, it is also involved in promoting inflammation, proliferation, fibrogenesis, and lipogenesis. Two pathways constitute the RAS with counter-balancing effects, which is the key to its regulation. The first axis (classical) is composed of angiotensin-converting enzyme (ACE), angiotensin (Ang) II, and angiotensin type 1 receptor (AT1R) as the main effector, which -when activated- increases the production of aldosterone and antidiuretic hormone, sympathetic nervous system tone, blood pressure, vasoconstriction, fibrosis, inflammation, and reactive oxygen species (ROS) production. Both systemic and local classical RAS´ within the brain are associated with cognitive impairment, cell death, and inflammation. The second axis (non-classical or alternative) includes ACE2, which converts Ang II to Ang-(1-7), a peptide molecule that activates Mas receptor (MasR) in charge of opposing Ang II/AT1R actions. Thus, the alternative RAS axis enhances cognition, synaptic remodeling, cell survival, cell signal transmission, and antioxidant/anti-inflammatory mechanisms in the brain. In a physiological state, both RAS axes remain balanced. However, some factors can dysregulate systemic and local RAS arms. The binding of SARS-CoV-2 to ACE2 causes the internalization and degradation of this enzyme, reducing its activity, and disrupting the balance of systemic and local RAS, which partially explain the appearance of some of the neurological symptoms associated with COVID-19. Therefore, this review aims to analyze the role of RAS in the development of the neurological effects due to SARS-CoV-2 infection. Moreover, we will discuss the RAS-molecular targets that could be used for therapeutic purposes to treat the short and long-term neurological COVID-19-related sequelae.